EDUCATIONAL ATTAINMENT OF CHILDREN IN FISHING COMMUNITIES: A Case Study of Pasar Baru, Sei Tualang Raso, Tanjung Balai City - Sirait, Mhd Thohirkan; Ritonga, Sakti (Prodi Tadris Ilmu Pengetahuan Sosial FITK UIN Sumatera Utara Medan, 2025)
This study aims to describe the level of education, identify obstacles, and analyze the strategies of fishermen’s families in supporting children’s education in Pasar Baru Village, Sei Tualang Raso District, Tanjung Balai City. The findings show an increase in parental awareness and participation in the importance of education, although they are still faced with structural obstacles such as economic limitations, difficult access to transportation, minimal educational facilities, and lack of social environmental support. The strategies implemented include financial management, emotional motivation, learning assistance, communication with schools, and utilization of government assistance. This study uses a descriptive qualitative approach with observation, interview, and documentation techniques. The main issue raised is the strong influence of socio-economic conditions on the sustainability of fishermen’s children’s education, so that a more inclusive and adaptive education policy is needed to meet the needs of coastal communities.